Meniscus repair failure risk does not differ by sex: a systematic review. Issue 2 (19th February 2020) - Hamilton, Christopher; Flanigan, David C; Patel, Kishan H; Lundy, Nathaniel; Blackwell, Ryan; Magnussen, Robert A
Abstract : Importance: Meniscus tears are common knee pathologies that are frequently treated with meniscus repair with a variety of techniques. Regardless of technique and implant choice, it is critical to understand and consider patient factors, including patient sex, which can influence outcome. Objective: We sought to determine if there is an effect of sex on failure risk following meniscus repair. Evidence review: A systematic review of the literature was undertaken to identify studies that reported failure risk independently for male and female patients. Meta-analyses were performed to identify the effect of patient sex on meniscus repair failure risk. Differences in patient-reported outcomes by sex were reported qualitatively. Findings: A total of 886 patients analysed were included in the 11 identified studies, including 556 males and 330 females. Meniscus repair failure was reported in 192 patients (21.7%). The failure risk was 21.1% in males and 21.5% in females. Meta-analyses demonstrated no significant difference in meniscus repair failure risk based on sex in neither the three studies that assessed repair success arthroscopically (p=0.66) nor the eight studies in which failure was defined with clinical assessment or as the need for repeat surgery (p=0.92). Conclusions and relevance: There are no significant differences in meniscus repair failure risk in male versus female patients in the existing literature. More published data are needed to evaluate patient-reported outcomes of meniscus repair based on sex. Level of evidence: IV, systematic review.